Asymmetric taxation and performance-based incentive contracts - Rainer Niemann (Center for Economic Studies and ifo Institute (CESifo), 2011)
This paper analyzes the effects of symmetric and asymmetric taxation on performance-based versus fixed remuneration contracts. I integrate a proportional corporation tax and a proportional wage tax into a binary principal-agent model. The wage tax increases the remuneration costs and makes the agent's employment less attractive. Thus, the principal tends to demand lower rather than higher effort or does not offer a contract at all. In contrast to the wage tax, the corporate tax is irrelevant for the optimal remuneration contract. Under asymmetric corporate taxation, the principal tends to offer contracts less frequently. Fixed remuneration contracts are penalized more heavily by asymmetric taxation than performance-based remuneration contracts.
Keywords: H25; M41; M52; 330; asymmetric taxation; loss-offset; principal-agent theory; corporate taxation; wage taxation; Leistungsorientierte Vergütung; Lohnsteuer; Körperschaftsteuer; Steuerwirkung; Prinzipal-Agent-Theorie; Theorie